Ade Digitization Of Algerian Manuscripts And Its Role In Achieving Knowledge Intersections And Benefiting From Them -The Humanities And Social Sciences As a Model (Journal of Informatics Education and Research, 2026)
Algerian manuscripts represent a symbol of civilizational and cultural advancement, as they reflect the roots of our Arab and Islamic identity and signify Algeria's scientific standing throughout the ages. Although Algerian libraries possess a number of these manuscripts, many of them remain stored in global treasuries and libraries.Activating the element of digitization is the means to overcome the difficulty of accessing these manuscripts in global treasuries and to facilitate their availability to researchers and those interested. Benefiting from modern technologies and artificial intelligence can reduce the gap between the manuscript and its confinement for intellectual property reasons, and between accessing it and making use of it.The utilization of Algerian manuscripts by researchers cannot be confined to one science or specialty; rather, the scope of sciences that benefit from them expands. A single manuscript in one field of science will certainly benefit other sciences; and each science has its way of drawing benefit from it.Therefore, we worked in this paper to highlight the role of digitizing Algerian manuscripts in achieving knowledge intersections among the sciences on the one hand, and in benefiting from this intersection on the other hand. We strengthened this research by presenting an example of knowledge intersection between the humanities and the social sciences when it comes to benefiting from a specific manuscript, and what this intersection can offer as a scientific contribution.